2013
DOI: 10.1155/2013/245357
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis for the Antirheumatic Effects of Huang-Lian-Jie-Du-Tang from a Network Perspective

Abstract: Huang-Lian-Jie-Du-Tang (HLJDT) is a classic TCM formula to clear “heat” and “poison” that exhibits antirheumatic activity. Here we investigated the therapeutic mechanisms of HLJDT at protein network level using bioinformatics approach. It was found that HLJDT shares 5 target proteins with 3 types of anti-RA drugs, and several pathways in immune system and bone formation are significantly regulated by HLJDT's components, suggesting the therapeutic effect of HLJDT on RA. By defining an antirheumatic effect score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“… Han et al (2017) showed that combination treatment with metformin, a classic antidiabetic drug, and Scutellariae Radix could improve obesity-induced insulin resistance and lipid metabolism by maintaining bile acid homeostasis through reducing the amount of harmful bacteria and altering the gut microbiota structure. From the perspective of holistic view of TCM, different herbs and multiple components in HLJDD could act on multiple targets and exert an enhancing synergistic effect ( Fang et al, 2013 ). Thus, the results based on the previous studies are partial and indirect.…”
Section: Introductionmentioning
confidence: 99%
“… Han et al (2017) showed that combination treatment with metformin, a classic antidiabetic drug, and Scutellariae Radix could improve obesity-induced insulin resistance and lipid metabolism by maintaining bile acid homeostasis through reducing the amount of harmful bacteria and altering the gut microbiota structure. From the perspective of holistic view of TCM, different herbs and multiple components in HLJDD could act on multiple targets and exert an enhancing synergistic effect ( Fang et al, 2013 ). Thus, the results based on the previous studies are partial and indirect.…”
Section: Introductionmentioning
confidence: 99%
“…The screening conditions were based on oral bioavailability (OB; ≥30%) and drug-likeness (DL ≥0.18), so as to obtain the drug composition and targets. Numerous recent studies have shown that the screening criteria can screen out effective pharmaceutical ingredients (19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to consider the relevance between the formula targets and disease genes for the elucidation of the associations between the formula and disease. The basic assumption is that if the formula is effective for the treatment of the disease, the formula targets are likely to be close to disease genes in the PPI network [ 55 ]. In this study, two network-based proximity measure approaches were used to capture such relatedness: the shortest path distance (SPD)[ 56 ] and a random walk with restart (RWR)[ 57 ] based scoring method.…”
Section: Methodsmentioning
confidence: 99%